Urban Ecology and Eco-Sustainability: A Framework for Urban Sustainability of Dhaka (Journal of Bangladesh Institute of Planners, 2016)
Ecological study targeting urban sustainability needs to ensure urban development in a manner that a city can achieve social and economic advances without damaging its natural environment. This paper evaluates and highlights the importance of urban ecology and eco-sustainability for sustainable use of ecosystem services within a city to ensure its urban sustainability. The study provides an ecological framework for urban sustainability of Dhaka primarily based on secondary data and information, although some information has been collected from primary sources as well. The paper illustrates that the image of Dhaka is not derived from its concrete parts like buildings, roads etc., it is much deeper and more fluid, that is, its people, pattern of spaces and activities therein, the relationship between the living and nonliving part of its environment, time, space and people. The ecological framework recognizes that the Plantation, Compensatory Greens or Garden, Green Urban Corridors, Green Urban Pockets or Vegetated Roofs, Green Roofs, Urban Landscaping, restoration of Natural Drainage System and creation of adequate water bodies are general approach to mitigate some of the losses of biomes, productivity and the biodiversity. The natural systems of Dhaka need to ensure its sustainability with the active participation of its community.JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 141-153